Efficient Synthesis of Benzothiazinone Analogues with Activity against Intracellular Mycobacterium tuberculosis. (23rd December 2021) - Richter, Adrian; Narula, Gagandeep; Rudolph, Ines; Seidel, Rüdiger W.; Wagner, Christoph; Av‐Gay, Yossef; Imming, Peter
Abstract: 8‐Nitrobenzothiazinones (BTZs) are a promising class of antimycobacterial agents currently under investigation in clinical trials. Starting from thiourea derivatives, a new synthetic pathway to BTZs was established. It allows the formation of the thiazinone ring system in one synthetic step and is applicable for preparation of a wide variety of BTZ analogues. The synthetic procedure furthermore facilitates the replacement of the sulphur atom in the thiazinone ring system by oxygen or nitrogen to afford the analogous benzoxazinone and quinazolinone systems. 36 BTZ analogues were prepared and tested in luminescence‐based assays for in vitro activity against Mycobacterium tuberculosis (Mtb) using the microdilution broth method and a high‐throughput macrophage infection assay. Abstract : We report the synthesis of antitubercular 8‐nitrobenzothiazinones and their antimycobacterial characterization. A synthesis using thiourea intermediates was established, and 35 analogues were prepared. Their antimycobacterial potential was investigated against Mycobacterium tuberculosis : minimal inhibitory concentrations (MICs) of all derivatives were determined in broth and in a macrophage infection model. Compounds with MICs of <50 nM could be described and characterized.